Excitation–Contraction Coupling in the Goldfish (Carassius auratus) Intact Heart - Bazmi, Maedeh; Escobar, Ariel L. (Frontiers in Physiology, 2020)
Cardiac physiology of fish models is an emerging field given the ease of genome editing and the development of transgenic models. Several studies have described the cardiac properties of Zebrafish (Denio rerio). The Goldfish (Carassius auratus) belongs to the same family as the Zebrafish and has emerged as an alternative model to study cardiac function. Here, we propose to acutely study electrophysiological and systolic Ca2+ signaling in intact Goldfish hearts. We assessed the Ca2+ dynamics and the electrophysiological cardiac function of Goldfish, Zebrafish, and mice models, using Pulsed Local Field Fluorescence Microscopy, intracellular microelectrodes, and flash photolysis in perfused hearts. We observed Goldfish ventricular action potentials (APs) and Ca2+ transients to be significantly longer when compared to the Zebrafish. The action potential half duration at 50% (APD50) of Goldfish was 370.38 ± 8.8 ms long, while in the Zebrafish they were observed to be only 83.9±9.4 ms. Additionally, the half duration of the Ca2+ transients was also longer for Goldfish (266.9±7.9 ms) compared to the Zebrafish (99.1±2.7 ms). Also, blocking of the L-type Ca2+ channels with nifedipine, revealed this current has a major role in defining the amplitude and the duration of Goldfish Ca2+ transients. Interestingly, nifedipine flash photolysis experiments in the intact heart identified whether or not the decrease in the amplitude of Ca2+ transients were due to shorter APs. Moreover, an increase in temperature and heart rate had a strong shortening effect on the AP and Ca2+ transients of Goldfish hearts. Furthermore, ryanodine (Ry) and thapsigargin (Tg) significantly reduced the amplitude of the Ca2+ transients, induced a prolongation in the APs, and altogether exhibited the degree to which the Ca2+ release from the sarcoplasmic reticulum (SR) contributed to the Ca2+ transients. We conclude the electrophysiological properties and Ca2+ signaling in intact Goldfish hearts strongly resembles the endocardial layer of larger mammals.